Comparison of Point Placement by Veterinary Professionals with Different Levels of Acupuncture Training in a Canine Cadaver Model - Toni Yang; Justin Shmalberg; Lindsay Hochman; Erin Miscioscia; Meghan Brumby; Kelsey McKenna; Amber Roth (Medical Association of Pharmacopuncture Institute, 2017)
Veterinary acupuncture is becoming increasingly implemented for various disease processes, with growing numbers of veterinarians pursuing advanced training to meet the rising demand for this relatively new intervention. Accurate acupoint placement remains challenging, with individual practitioners relying on varying methods of point identification, often compounded by the transpositional nature of points for companion animals. The aim of this study was to assess for differences in acupuncture needle placement of select points between veterinary professionals with three different levels of acupuncture training in an academic teaching environment. Seven participants placed a total of six acupoints on a canine cadaver. Digital radiography was used to document each participant's point placement. Each participant's point location was then compared to a control "correct" point, and the distance between the two points was measured. A significant difference in placement accuracy was identified between the participants when grouped by training level (p = 0.03). These results indicate that veterinary patients receiving acupuncture treatment from veterinarians with different levels of training may subsequently experience varying effects, although further studies are warranted on more specific acupoint description as well as the clinical implications of needle placement accuracy.